2012
DOI: 10.1111/j.1440-1835.2011.00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolic, size‐fractionated phenolics and fucoxanthin content of tropical Sargassaceae (Fucales, Phaeophyceae) from the South Pacific Ocean: Spatial and specific variability

Abstract: International audienceThis innovative study investigates 18 Turbinaria and Sargassum brown seaweed samples from three archipelagos of the South West Pacific Ocean. The phenolic content of crude and size-fractionated extracts was determined by the Folin-Ciocalteu method; fucoxanthin was measured using high performance liquid chromatography. Although the phenolic content proved to be low for the species of both genera tested, the levels in the species of Turbinaria were higher than those of Sargassum tested, exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 69 publications
2
33
0
2
Order By: Relevance
“…The pool of phenolic compounds from Sargassaceae species is composed by a majority of small molecules (<2000 Da) (without taking in consideration C. baccata from Pointe du Diable in summer 2007). Similar ratios were obtained in tropical Sargassaceae species from South Pacific islands (Le Lann et al, 2012): oligophenols, i.e. phenolic compounds with low molecular weight, less than 2000 Da, dominated the pool of phenolic compounds.…”
Section: Phenolic Content In Sargassaceae Speciessupporting
confidence: 68%
See 1 more Smart Citation
“…The pool of phenolic compounds from Sargassaceae species is composed by a majority of small molecules (<2000 Da) (without taking in consideration C. baccata from Pointe du Diable in summer 2007). Similar ratios were obtained in tropical Sargassaceae species from South Pacific islands (Le Lann et al, 2012): oligophenols, i.e. phenolic compounds with low molecular weight, less than 2000 Da, dominated the pool of phenolic compounds.…”
Section: Phenolic Content In Sargassaceae Speciessupporting
confidence: 68%
“…Bjerke et al, 2005;Fairhead et al, 2006). Phenolic content in Phaeophyceae is governed by various environmental factors such as factors related to seasonality Stiger et al, 2004;Plouguerné et al, 2006), light (Abdala-Díaz et al, 2006), depth in the water column (Le Lann et al, 2012) and nutrient concentration (Yates and Peckol, 1993). Most studies demonstrated the biological activities of phlorotannins considering these molecules as a pool.…”
Section: Introductionmentioning
confidence: 98%
“…The different fucoxanthin contents in different seasons are mainly due to light exposure and temperature fluctuations (Nomura et al 2013). According to the results in Table 1, fucoxanthin content in N. zanardinii and C. indica is significantly higher than other species from tropical areas (Nomura et al 2013;Lann et al 2012;Jaswir et al 2013a;Fung et al 2013;Terasaki et al 2009). It is likely that fucoxanthin in the studied species not only has a light harvesting role but also acts as a strong photoprotectant.…”
Section: Discussionmentioning
confidence: 85%
“…Variation in TPC values of marine macroalgae could be influenced by extrinsic factors (such as herbivory pressure, irradiance, depth, salinity and nutrients), by intrinsic factors (morphology, age and reproductive stage), but also by the type of solvent used in the extraction of the phenolic compounds (Chew et al 2008, Ganesan et al 2011, Lann et al 2012 …”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%